2007
DOI: 10.1177/1052562905282023
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Entrepreneurial Drive in Business Education: An Attitudinal Approach

Abstract: Drawing from research in individual characteristics of entrepreneurs and the theory of planned behavior from social psychology literature, this study identifies attitudinal dimensions of entrepreneurial drive (ED), proposes a model, and develops and tests an instrument to measure it. Resultsshow that students differentiate among five attitudes that have been found to promote entrepreneurial behavior in prior research, namely, preference for innovation, nonconformity, proactive disposition, self-efficacy, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
174
1
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(194 citation statements)
references
References 39 publications
10
174
1
9
Order By: Relevance
“…A c c e p t e d D r a f t Florin et al (2007) did not confirm any association between the Entrepreneurial Drive scale and entrepreneurial intention or entrepreneurial behavior. They did find that overall Entrepreneurial Drive was significantly higher among seniors than among freshman, and found no significant difference based on gender.…”
Section: A J P Ementioning
confidence: 82%
See 2 more Smart Citations
“…A c c e p t e d D r a f t Florin et al (2007) did not confirm any association between the Entrepreneurial Drive scale and entrepreneurial intention or entrepreneurial behavior. They did find that overall Entrepreneurial Drive was significantly higher among seniors than among freshman, and found no significant difference based on gender.…”
Section: A J P Ementioning
confidence: 82%
“…13 15 The included entrepreneurs had each started more than one business, with at least one initiated within the past five years. 13 Florin et al (2007) selected 42 of the highest loading and student appropriate items out of the original 75 validated items from the Entrepreneurial Attitude Orientation Scale. Entrepreneur and business specific items were eliminated because of the intended use in students.…”
Section: R a F Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore it is suggested that entrepreneurship education be integrated in the academic curricula at all levels from elementary school to university (Stevenson & Lundstrom, 2001). As emphasized by Florin, Karri, and Rossiter (2007), it is not enough to teach necessary skills for entrepreneurship but, rather, it is essential to develop and enhance an "entrepreneurial drive". "Entrepreneurial drive" means how individual perceive the desirability and feasibility to pursue opportunities in a proactive manner and respond to challenging tasks, needs and obstacles in an innovative and creative way.…”
Section: Journal Of Management Researchmentioning
confidence: 99%
“…Florin, Karri and Rossiter (2007) developed an instrument measuring entrepreneurial drive based upon preference of innovation, nonconformity, proactive disposition, self-efficacy and achievement motivation.…”
Section: Conceptual Frameworkmentioning
confidence: 99%